2020
DOI: 10.1097/md.0000000000023663
|View full text |Cite
|
Sign up to set email alerts
|

Association of toll-like receptor polymorphisms with acquisition of HIV infection and clinical findings

Abstract: Background: To find the relationship between toll-like receptor (TLR) gene variants and human immunodeficiency virus (HIV) infection and clinical findings, which could inform clinical decisions and vaccination strategies. Method: Four databases were searched for articles that were published on or before Jul.1, 2020. Review Manager 5.3 software was applied to perform meta-analysis to explore. Results: A total of 10 studies involving 20 genes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…However, interpretations of how TLR SNPs affect the immune response are further complicated by other factors including ethnicity, gender, and the possibility of multigenic effects. The molecular mechanisms by which SNPs influence TLR receptor functioning are unclear for many TLRs [ 54 ]. Recent research on TLR polymorphisms and their correlation with various outcomes, published over the last five years, is presented in this review ( Table S1 ).…”
Section: Toll-like Receptorsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, interpretations of how TLR SNPs affect the immune response are further complicated by other factors including ethnicity, gender, and the possibility of multigenic effects. The molecular mechanisms by which SNPs influence TLR receptor functioning are unclear for many TLRs [ 54 ]. Recent research on TLR polymorphisms and their correlation with various outcomes, published over the last five years, is presented in this review ( Table S1 ).…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…However, some studies emphasise that a role of TLR2 in HIV-1 disease progression rates (CD4+ 200 cells/μL) may be distinct from this gene’s impact on infection susceptibility [ 58 ]. In 2020, Shi et al conducted a systematic review and meta-analysis of 10 studies covering 20 genes and showed a correlation between clinical findings in HIV-infected persons and TLR2 −196 to −174 Ins/Del [ 54 ]. In 2022, TLR2 , TLR4 , and TLR9 genetic diversity in HIV-1-infected patients with and without tuberculosis coinfection was studied by Kaushik et al However, no significant differences in the frequency of the C2180T allele between the healthy and patient subcategories were found.…”
Section: Toll-like Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings suggest a potentially important role of host TLR9 polymorphisms in HIV disease progression [ 8 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The TLR9 rs352140 GG genotype was associated with an increased risk of HIV infection, disease progression, and CD4 count [ 20 , 27 , 29 ]. Mutation present in at least one allele of the TLR9 1635A/G SNP (rs352140) was found to be associated with increased CMV acquisition in HIV-exposed infants [ 19 ].…”
Section: Introductionmentioning
confidence: 99%